Trans-axillary approach in surgery for thoracic outlet syndrome - Yalcinkaya, Serhat; Eris, Cuneyt; Goncu, Tugrul (The European Research Journal, 2016)
Background. Thoracic outlet syndrome may be due to various reasons and be classified as neurogenic, arterial, and venous thoracic outlet syndrome. The surgical treatment of neurogenic thoracic outlet syndrome can be performed using either a trans-axillary or a supraclavicular approach. The aim of this study is to report on such patients operated in a single institution by a single thoracic surgeon using trans-axillary approach. Methods. The patient files were screened for patients operated due to neurogenic thoracic outlet syndrome related symptoms between September 1, 2002 and April 1, 2015 in the Department of Thoracic Surgery of Bursa Yuksek Ihtisas Training and Research Hospital. Results. There were 22 female and five male patients with an average age of 31.9±11.7 years. The most common symptom was pain in the affected limb and shoulder (n=29). Of the diagnostic maneuvers abduction external rotation (Roos) test was the most frequently found positive test (n=27). Nerve conduction velocity studies revealed an average ulnar nerve conduction velocity of 62.7±6.6 m/s. Limited pneumothorax uneventfully resolved in 2 days was seen following 12 operations. Conclusion. We conclude that trans-axillary approach may provide good exposure with favorable opportunity to excise the 1st and the cervical rib, and neurolysis with a low rate of complication.